Text structures from fairy tales truisms that help students write about abstract concepts-- and live happily ever after, grades 4-12 - Bernabei, Gretchen S.; Reimer, Judi (Corwin literacy., 2019)
Put text structures to work and soon your students will be writing happily ever after. Thirty-five lessons centered on classic fairy tales give students the focused practice they need to produce effective analytical writing on demand-and in any situation. Designed to be used by students of all ages, each lesson includes a writing prompt and a planning framework that leads students to organize writing through a text structure.